Peningkatan kemampuan bacaan salat dengan metode reading aloud MIM Blagung Simo - Agus Salim Salim; Joko Subando Joko; Meti Fatimah Meti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this study was to determine the increase in learning outcomes in the ability to recite prayers using the reading-aloud method. This research uses classroom action research (CAR). In PTK the research phase consists of four stages, namely planning, action implementation, observation, and reflection. The research results show that applying the reading-aloud method can improve the learning outcomes of prayer reading skills. This is indicated by the average initial test result of 66.58, in cycle I it became 76.056 and in cycle II it rose to 94.25. The level of learning completeness also increased from the initial test, which was 11.11%, in cycle I it became 58.33% and in cycle II it increased again to 100%. IV MIM Blabung Simo.